Censorship and Freedom of Speech in two Scenes of Aristophanes’ Acharnians - Agostini, Cristina de Souza (Revista Archai, 2024)
This paper aims to show a comparative analysis of two scenes of the Aristophanic comedy Acharnians. On the one hand, I discuss the role of Amphitheus character, and on the other hand, I consider the ambassadors’ speech. By opposing these two play’s scenes, I support that democratic decision in assembly is a fertile ground to censure speeches about the good application of policies headed to the common good, and at the same time, it consecrates the freedom of speech of those who have personalist agendas at the expense of demos’ poverty. Thus, the speech in favor of the Peloponnesian War’s maintenance is a smokescreen for the political leaders’ enrichment. And because this is the only one for which exists freedom of expression, whereas its opposite, i.e., the pacifist speech, must be censored, even with violence.